NATO Contributions to European Environmental Security - Butts, Kent H. (1993)
Environmental issues are promoting instability and conflict at an ever increasing rate. Forward-thinking international security strategists suggest that these catalytic issues be addressed before they lead costly conflict. The U.S. Department of Defense has committed its to using DOD assets to address these environmental problems. This study builds upon these visionary concepts to recommend that NATO develop an environmental assistance program to address issues that threaten stability in regions strategically important to European security. With NATO searching for a new mission to demonstrate its relevance in the post-cold war era, such a program has great potential benefit in helping to mitigate significant environment problems. It would also allow NATO to promote military-to-military contacts and enhance communication with former adversaries. NATO, Post-cold war era, Environmental security assistance program, Alliance strategic concept, Military-to-military contacts, Environmental degradation, CCMS, NACC.